2004
DOI: 10.1002/adma.200306142
|View full text |Cite
|
Sign up to set email alerts
|

Material Storage Mechanism in Porous Nanocarbon

Abstract: Material storage in the inner spaces of nanocarbon materials is visualized for the first time. It is shown that creating paths of a specific size to the inner space (see Figure) is indispensable for material storage in carbon nanopores, and that the adsorption rate for fullerene molecules is largely dependent on the nanoscale curvature of the graphitic planes composing the nanospaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
93
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 17 publications
4
93
0
Order By: Relevance
“…[60]Fullerene quickly enters the internal space of oxNH580 through the holes (22,23), and we exploited this property of fullerene to show that the clusters form on most of the hole openings. Thus, oxNH580 was first treated with methanolic Gd(OAc) 3 , as described above, followed by a toluene solution of [60]fullerene: TEM observation of several of the dahlia aggregates (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[60]Fullerene quickly enters the internal space of oxNH580 through the holes (22,23), and we exploited this property of fullerene to show that the clusters form on most of the hole openings. Thus, oxNH580 was first treated with methanolic Gd(OAc) 3 , as described above, followed by a toluene solution of [60]fullerene: TEM observation of several of the dahlia aggregates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sample was sucked dry quickly by filtration paper and analyzed by TEM. Details of the method have been described (22,23).…”
Section: Treatment Of Gdoxnh580 With [60]mentioning
confidence: 99%
See 1 more Smart Citation
“…Thousands of SWNHox partially coalesce to form an 80-to 100-nm spherical aggregate (2), and this aggregate is expected to have enhanced permeability and retention properties (26,27) that make SWNHox effective for passive delivery of drugs to tumors. The holes of SWNHox observed with transmission electron microscopy (TEM) are 1-3 nm in diameter (28), and their pore sizes distributed in a range of 1-5 nm, showing a maximum at Ϸ2 nm (29), so that ZnPc [size: Ϸ1.4 nm (30)], similar to other molecules (7,8,(31)(32)(33), can pass into the SWNHox tubules. The edges of the SWNHox holes have many carboxyl groups that can be used to attach biological materials, such as proteins, to enhance the biocompatibility of SWNHox (34).…”
mentioning
confidence: 99%
“…We have tested inserting or doping C60 molecules into nanocarbon materials, namely carbon nanohorns, which is similar to SCNTs. The doping was carried out in solution instead of conventional vapor phase that is not applicable to drugs [4]. We have confirmed that after oxidizing properly as-grown carbon nanohorns, we doped them with C60 and examined adsorption and release characteristics of them.…”
mentioning
confidence: 80%